Structural and Functional analysis of Staphylococcus aureus NADP-dependent IDH and its comparison with Bacterial and Human NADPdependent IDH - Prasad, Uppu Venkateswara (Biomedical Informatics, 2014)
Staphylococcus aureus a natural inhabitant of nasopharyngeal tract mainly survives as biofilms and possess complete Krebs cycle which plays major role in its pathogenesis. This TCA cycle is regulated by Isocitrate dehydrogenase (IDH) we have earlier cloned, sequenced (HM067707), expressed and characterized this enzyme from S. aureus ATCC12600. We have observed only one type of IDH in all the strains of S. aureus which dictates the flow of carbon thereby controlling the virulence and biofilm formation, this phenomenon is variable among bacteria. Therefore in the present study comparative structural and functional analysis of IDH was undertaken. As the crystal structure of S. aureus IDH was not available therefore using the deduced amino sequence of complete gene the 3D structure of IDH was built in Modeller 9v8. The PROCHECK and ProSAweb analysis showed the built structure was close to the crystal structure of Bacillus subtilis. This structure when superimposed with other bacterial IDH structures exhibited extensive structural variations as evidenced from the RMSD values correlating with extensive sequential variations. Only 24% sequence identity was observed with both human NADP dependent IDHs (PDB: 1T09 and 1T0L) and the structural comparative studies indicated extensive structural variations with an RMSD values of 14.284Å and 10.073Å respectively. Docking of isocitrate to both human IDHs and S. aureus IDH structures showed docking scores of -11.6169 and -10.973 respectively clearly indicating higher binding affinity of isocitrate to human IDH.